2022
DOI: 10.3390/ijerph19127257
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 Antibodies in Africa: A Systematic Review and Meta-Analysis

Abstract: A reliable estimate of SARS-CoV-2-specific antibodies is increasingly important to track the spread of infection and define the true burden of the ongoing COVID-19 pandemic. A systematic review and a meta-analysis were conducted with the objective of estimating the seroprevalence of SARS-CoV-2 infection in Africa. A systematic search of the PubMed, Scopus, Web of Science and Google Scholar electronic databases was conducted. Thirty-five eligible studies were included. Using meta-analysis of proportions, the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…Seroprevalence was highest in studies conducted in Central Africa, as well as among African-Americans, and antibody prevalence was highest among those under 30 years of age. 13 , 29 It has been shown that LFIA assays may have a lower performance than enzyme-linked immunosorbent assays (ELISA) as well as chemiluminescent immunosorbent assays (CLIA), and the sensitivity of LFIA tests may be related to the profile of the infected patients. 30–32 To address this gap, anti-N was also performed by the CLIA method, and the results revealed that 91.9% of the participants developed antibodies against protein N. This value was higher than those found by LFIA which could be justified as the CLIA method is more efficient and it has been shown that the sensitivity of LFIA is higher in symptomatic hospitalised patients than in asymptomatic patients, 30 which constitutes the population of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence was highest in studies conducted in Central Africa, as well as among African-Americans, and antibody prevalence was highest among those under 30 years of age. 13 , 29 It has been shown that LFIA assays may have a lower performance than enzyme-linked immunosorbent assays (ELISA) as well as chemiluminescent immunosorbent assays (CLIA), and the sensitivity of LFIA tests may be related to the profile of the infected patients. 30–32 To address this gap, anti-N was also performed by the CLIA method, and the results revealed that 91.9% of the participants developed antibodies against protein N. This value was higher than those found by LFIA which could be justified as the CLIA method is more efficient and it has been shown that the sensitivity of LFIA is higher in symptomatic hospitalised patients than in asymptomatic patients, 30 which constitutes the population of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted regarding the circulation of SARS-CoV-2 in some African countries revealed prevalence ranging from 19.1% to 65.0% in the general population [5][6][7][8][9][10][11][12][13][14][15][16] and 4.0% to 63.0% in specific populations [17][18][19][20][21][22][23][24]. Results of a recent study using a meta-analysis of proportions show that the overall seroprevalence of anti-SARS-CoV-2 antibodies in Africa was 16.0% (95% confidence interval [CI]: 13.1-18.9%) in the period 2020-2021 [25]. Based on these statistics, it is safe to say that the virus has spread widely in African countries, in contrast to the estimations published by governments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there has been substantial evidence that approximately 40% of all SARS‐CoV‐2 infections are thought to be asymptomatic, and active surveillance for infections without symptoms is limited even now, large number of cases might be unnoticed/might go undocumented 7,8 . Cognizant of this fact, several large population‐based seroprevalence studies have been conducted in COVID‐19 hotspots in Europe, 9–11 America, 12,13 Asia, 14–17 and in Africa 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Cognizant of this fact, several large population-based seroprevalence studies have been conducted in COVID-19 hotspots in Europe, [9][10][11] America, 12,13 Asia, [14][15][16][17] and in Africa. [18][19][20] Population-based serological data are essential for understanding the overall distribution, presence of hotspots, prevalence of subclinical infections, and the population's herd immunity against SARS-CoV-2. 21,22 The point at which the proportion of susceptible individuals falls below the threshold needed for transmission is known as the "herd immunity threshold."…”
Section: Introductionmentioning
confidence: 99%